2018
DOI: 10.1002/chem.201800423
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Insights into Selective Oxidation of Polyaromatic Compounds using RICO Chemistry

Abstract: Ruthenium-ion-catalyzed oxidation (RICO) of polyaromatic hydrocarbons (PAHs) has been studied in detail using experimental and computational approaches to explore the reaction mechanism. DFT calculations show that regioselectivity in these reactions can be understood in terms of the preservation of aromaticity in the initial formation of a [3+2] metallocycle intermediate at the most-isolated double bond. We identify two competing pathways: C-C bond cleavage leading to a dialdehyde and C-H activation followed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 47 publications
1
10
0
Order By: Relevance
“…8). This type of reaction has been studied for OsO 4 53,54 or RuO 4 55 on simple aromatic systems or double bonds. DFT calculations confirmed the good affinity between the ditopic ligand of UiO-66-NH 2 and RuO 4 , through strong hydrogen bonding between the porous framework (from NH 2 groups connected to neighboring ligands) and the gaseous species in intermediate 1.…”
Section: Resultsmentioning
confidence: 99%
“…8). This type of reaction has been studied for OsO 4 53,54 or RuO 4 55 on simple aromatic systems or double bonds. DFT calculations confirmed the good affinity between the ditopic ligand of UiO-66-NH 2 and RuO 4 , through strong hydrogen bonding between the porous framework (from NH 2 groups connected to neighboring ligands) and the gaseous species in intermediate 1.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, using RICO chemistry, we found that the number of aromatic rings in a substituted PAH determines the reaction rate, with larger aromatic systems reacting faster than smaller ones. 13 In the case of the tungsten/peroxide catalyst system, when naphthalene, (12), phenanthrene, (13), and pyrene, (14), were used as substrates, it was also found that the reaction rate increased with the increasing number of fused aromatic rings (Fig. 2).…”
Section: Kinetic Studiesmentioning
confidence: 94%
“…11 In our RICO work, selectivity was not affected by the choice of solvent for 2-ethylnaphtahlene oxidation (CH 3 CN, H 2 O or CH 3 CN, DCM, H 2 O). 11,14 However, it was shown that, using RICO, the solvent affects the selectivity for oxidation of molecules with three or more aromatic rings, giving a lower degree of aliphatic carbon oxidation in the presence of acetonitrile. 13 A possible explanation for the change of selectivity with solvent for 2-ethylnaphtalene using the H 2 WO 4 /H 2 O 2 system could be the distribution of the tungsten complex in the reaction medium.…”
Section: Oxidation Of 2-ethylnaphthalenementioning
confidence: 99%
See 2 more Smart Citations